Acceptance and uses of eSports as an official sport among youth in Malacca / Muhammad Naim Aminuddin - Aminuddin, Muhammad Naim (Faculty of Business and Management, 2019)
Although many developed countries had long started to accept gaming as one of the educational and recreational activities, Malaysia is yet to see that type of development. The only progress we made were by establishing the APU eSports Malaysia Academy in 2017 and nothing else had improved afterward. Therefore, the main objective of this research is to investigate the relationship between the acceptance and use of eSports as an official sport and the independent variable derived from the UTAUT Model which are performance expectancy, social influence and facilitating condition among the youth in Malacca. The research design for this research is through employing survey research design and the primary data are collected by distributing the questionnaire to the target respondents which is youth respondents aged from 15 years old to 40 years old in Malacca. 150 respondents were collected by using convenience sampling method. The data then were analyzed by using the Statistical Package for Social Science (SPSS) version 22. In this research, it was found out that all three variables are significant and were having strong uphill linear relationship with the dependent variables and it reveal that those three factors contribute 74.3 percent toward explaining the dependent variable which is the acceptance and uses of esport as an official sport among youth in Malacca. Recommendations and directions are provided to assist the future researcher to conduct their research.